APPLICATION OF THE CONCEPT OF GENDER EQUALITY IN CHILDREN'S PARKING PATTERNS - Putri Amalia Zubaedah (Green Publisher, 2022)
Parents, especially children in parenting, must achieve gender equality as early as possible. Therefore, the purpose of this study is to examine and describe the application of the concept of gender equality in parenting. The research method used in this study is a qualitative descriptive method. The type of data used in this research is qualitative data, which is divided into primary data and secondary data. Sources of data obtained through library research techniques refer to sources available online and offline, such as scientific journals, books, and news from trusted sources. The results of the study concluded that the Mubdalam concept is one of the concepts of gender equality that emphasizes partnership and cooperation of two people involved, contributing to each other according to their respective abilities, so that both parties benefit from the collaboration. The principle of interdependence is the basis of the concept of mublah, which is in line with human nature not to live alone but side by side with others. Allah SWT. Human men and women were created to be the subject of life, so that the status of both is the same. This concept is a related concept that will be applied in child care to provide children with an initial understanding of gender equality.